The Heterogeneity of Small, Mid-Scale, and Large-Scale Curly Red Chili Farming In Megamendung, Indonesia - Haryanto, Lorenta In; Harahap, Mely Dayanty; Putri, Dessy Iriani (Jambura Agribusiness Journal, 2023)
The change in land tenure and the shrinking size of agricultural land in Indonesia are recurring discussion topics. For farming to be sustainable, higher profit must be gained, particularly as a backup in the increasing number of small farms. This study aims to examine the farming practices of curly red chili at three farming scale levels: large-scale, mid-scale, and small farms. The observations, surveys, and interviews were conducted to obtain curly red chili production data during the wet season (December 2021 - March 2022) in Megamendung Sub-district. The farm parameters were presented descriptively; conversely, the farm's efficiency was measured using the R/C ratio of explicit cost and implicit costs. As many as 30 farmers are chosen using a purposive sampling technique. The study revealed that the profits gained by farmers depend on the farms scale with the largest share of large-scale farms, followed by mid-scale and small farms, whose R/C ratios on explicit cost were 9.50, 9.03, and 7.50, respectively. Mid-scale farms benefit from the high selling prices of the selected marketing channels; on the other hand, large-scale farms benefit from efficient production factors. Evidence shows that small farms may utilize both production factors and distribution channels less effectively. It is important for the government to consider implementing land consolidation for fragmented land like this. Land consolidation will assist farmers in the process of managing land and production systems in groups to make efficient use of farming production factors.